Fundamentals of machine theory and mechanisms / Antonio Simón Mata...[al et] - Bataller Torras, Alex,
This book covers the basic contents for an introductory course in Mechanism and Machine Theory. The topics dealt with are: kinematic and dynamic analysis of machines, introduction to vibratory behaviour, rotor and piston balance, kinematics of gears, ordinary and planetary gear trains and synthesis of planar mechanisms. A new approach to dimensional synthesis of mechanisms based on turning functions has been added for closed and open path generation using an optimization method based on evolutionary algorithms. The text, developed by a group of experts in kinematics and dynamics of mechanisms at the University of Málaga, Spain, is clear and is supported by more than 350 images. More than 60 outlined and explained problems have been included to clarify the theoretical concepts.